2010
DOI: 10.1115/1.4000875
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Measurement of Freezing-Induced Deformation of Engineered Tissues

Abstract: In order to cryopreserve functional engineered tissues (ETs), the microstructure of the extracellular matrix (ECM) should be maintained as well as the cellular viability since the functionality is closely related to the ECM microstructure. Since the post-thaw ECM microstructure is determined by the deformation of ETs during cryopreservation, freezing-induced deformation of ETs was measured with a newly developed quantum dot (QD)-mediated cell image deformetry system using dermal equivalents as a model tissue. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(68 citation statements)
references
References 42 publications
3
65
0
Order By: Relevance
“…We think that the Co-CACH intraprocedural targeting efficacy is the essence of safety. To us, the ice margin assists with the deposition of the selected LMW free drugs mixture and with a marginal fluid flow to which factors such as a peripheral increased hydraulic conductivity, an augmented extracellular fluid fraction triggered by the freezing, the volume of injectate, 12,13,31 and a more central fluid-impervious hard ice 6,16,32 contribute. The slush ice region whose outer rim is CT imageable would act as a tunable fluid-channeling network that can be switched on and off with time-adjusted freeze and thaw sequences.…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…We think that the Co-CACH intraprocedural targeting efficacy is the essence of safety. To us, the ice margin assists with the deposition of the selected LMW free drugs mixture and with a marginal fluid flow to which factors such as a peripheral increased hydraulic conductivity, an augmented extracellular fluid fraction triggered by the freezing, the volume of injectate, 12,13,31 and a more central fluid-impervious hard ice 6,16,32 contribute. The slush ice region whose outer rim is CT imageable would act as a tunable fluid-channeling network that can be switched on and off with time-adjusted freeze and thaw sequences.…”
Section: Safetymentioning
confidence: 99%
“…9,10 However, it is not known which timing, route of administration, formulation, or dosing for the associated cytotoxic drugs is best for improving the effectiveness and predictability of the cryoablative ice margin. [11][12][13] Many studies use drugs formulated with vehicles such as a matrix, capsule, or nanoparticle that facilitate tumor targeting, drug residence, slow release rate, and intracellular uptake. Promising combination therapy associated with nanoparticleencapsulated doxorubicin and CA 14 demonstrate enhanced eradication of cancer stem cells (CSTs) in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The cells were then trypsinized and used to prepare the engineered tissues. The cells were labeled with another smaller size particle, 20 nm diameter quantum dots (Qtracker 655, Invitrogen, Carlsbad, CA), according to the protocol described earlier [23].…”
Section: Tissue Equivalents With Fluorescent Particle-labeledmentioning
confidence: 99%
“…These studies were based on a hypothesis that biological tissues can be approximated as a poroelastic material that consists of fibrous collagen ECM saturated with interstitial fluid. These studies suggest that the volumetric expansion associated with the freezing of the interstitial fluid induces complex interactions among the ECM, fluid and cells, and these interactions result in the enlarged pore structure of the ECM and extrusion of the interstitial fluid post-thaw [7,[21][22][23]. A measurement technique was developed [23] to quantify spatiotemporal deformation inside the ET, and these studies found that ECM deformation during freezing can be correlated to the change in ECM microstructure post-thaw [7,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation